A Comparative Analysis of Mergers and Acquisitions and its Impact on Financial Performance of Commercial Banks - Dongol, Padam; Yadav, Manisha (MVIC Journal of Management and Information Technology, 2025)
This study examines the impact of mergers and acquisitions (M&A) on the financial performance of commercial banks in Nepal, focusing on pre- and post-merger financial metrics. Using Global IME Bank and Kumari Bank Limited as case studies, financial data from seven quarters before and after their merger in Poush 2079 were analyzed. Performance was measured using Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). A paired sample t-test revealed significant declines in all metrics post-merger, indicating a negative short-term financial impact. Global IME Bank experienced decreases in ROA (-28.48%), ROE (-32.19%), and NPM (-28.69%), while Kumari Bank showed even sharper declines in ROA (-56.68%), ROE (-53.43%), and NPM (-52.27%). These findings suggest operational inefficiencies, restructuring costs, and integration challenges contributed to diminished profitability and asset efficiency in the short term. The study highlights the complexity of achieving synergies in M&A and underscores the importance of effective integration strategies, thorough planning, and stakeholder management to mitigate financial pressure and operational disruptions. While M&A can offer long-term benefits such as market expansion and improved competitiveness, their short-term impact on financial performance requires strategic interventions to maximize synergies and minimize disruptions.